Coagulation and disinfection by-products formation potential of extracellular and intracellular matter of algae and cyanobacteria. (April 2020) - Zhao, Ziming; Sun, Wenjun; Ray, Ajay K.; Mao, Ted; Ray, Madhumita B.
Abstract: Coagulation and flocculation can remove particulate algal cells effectively; however, they are not very effective for removing dissolved algal organic matter (AOM) in drinking water plants. In this work, optimum coagulation conditions using alum for both extracellular and intracellular organic matter of six different algal and cyanobacterial species were determined. Different coagulation conditions such as alum dosage, pH, and initial dissolved organic carbon (DOC) were tested. Hydrophobicity, hydrophilicty, and transphilicity of the cellular materials were determined using resin fractionation method. The removal of DOC by coagulation correlated well with the hydrophobicity of the AOM. The disinfection by-product formation potential (DBPFP) of various fractions of AOM was determined after coagulation. Although, higher removal occurred for hydrophobic AOM during coagulation, specific DBPFP, which varied from 10 to 147 μg/mg-C was higher for hydrophobic AOM. Of all the six species, highest DBPFP occurred for Phaeodactylum tricornutum, an abundant marine diatom species, but is increasingly found in surface water. Highlights: Only a maximum of 60% removal of algal organic matter (AOM) occurred by coagulation. AOM removal by coagulation correlated well with the hydrophobicity of AOM. The hydrophobic fractions of AOM contributed maximum to the DBP formation. DBP formation potential is moderately correlated to SUVA values of AOM.